Erythroderma as a manifestation of leprosy - Renato Luiz Baldissera; Guilherme Athanasio Shwetz; José Fillus Neto; Noely do Rocio Vigo (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Erythroderma consists of erythema and scaling involving most or all of the body surface. This generalized eruption may be idiopathic, drug-induced or secondary to cutaneous or systemic disease. A 71-year-old man is reported presenting generalized erythema and desquamation with deck-chair sign, nail dystrophy, and plantar ulcers associated with loss of local tactile sensitivity. Biopsies from three different sites demonstrated diffuse lymphocytic infiltrate with incipient granulomas. Fite-Faraco staining showed numerous isolated bacilli and globi. The skin smear was positive. Clinical and pathological diagnosis of borderline lepromatous leprosy was confirmed. This report demonstrates that chronic multibacillary leprosy can manifest as erythroderma and thus should be included in the differential diagnosis.